2012
DOI: 10.1111/j.2042-3306.2011.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine adaptations in the foal over the perinatal period

Abstract: SummaryIn adapting to life ex utero, the foal encounters a number of physiological challenges. It has to assume the nutritional, respiratory and excretory functions of the placenta and activate full regulatory control over its own internal environment for the first time. To achieve this, there must be structural and functional changes to a wide range of tissues including several endocrine glands. In most species, including the horse, these maturational changes begin in late gestation and continue into the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 81 publications
(378 reference statements)
1
36
0
13
Order By: Relevance
“…The concentrations we found in Martina Franca donkeys are similar to those reported in resting horses [5,9,15,16]. Fowden et al [17] studied plasma catecholamine concentration variation in newborn pony foals and found that after birth adrenaline and noradrenaline concentrations are over 3000 ng/L and they decreased within 6-8 h to basal concentrations of 200 ng/L, similar to those observed in donkey in the current paper. We found no differences in catecholamine concentrations between male and female donkeys.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The concentrations we found in Martina Franca donkeys are similar to those reported in resting horses [5,9,15,16]. Fowden et al [17] studied plasma catecholamine concentration variation in newborn pony foals and found that after birth adrenaline and noradrenaline concentrations are over 3000 ng/L and they decreased within 6-8 h to basal concentrations of 200 ng/L, similar to those observed in donkey in the current paper. We found no differences in catecholamine concentrations between male and female donkeys.…”
Section: Discussionsupporting
confidence: 90%
“…sports animals), transport and lairage [14] in horses but there are no data on plasma catecholamine concentrations in donkeys. Fowden et al [17] studied plasma catecholamine concentration variation in newborn pony foals and found that after birth adrenaline and noradrenaline concentrations are over 3000 ng/L and they decreased in donkey in the current paper. Fowden et al [17] studied plasma catecholamine concentration variation in newborn pony foals and found that after birth adrenaline and noradrenaline concentrations are over 3000 ng/L and they decreased in donkey in the current paper.…”
Section: Discussionmentioning
confidence: 52%
“…Maturation of the equine fetal HPAA in terms of cortisol secretion occurs late in gestation compared to other species . Fetal cortisol concentrations increase rapidly 4‐7 days before delivery when 17α‐hydroxylase expression rises in the zona fasciculata .…”
Section: Discussionmentioning
confidence: 99%
“…2003). The influence of inflammatory mediators, cardiovascular/cord compromise, hypoxia and other disease processes are poorly documented in horses, but may have interesting correlations with human perinatal disease and are discussed further in other reviews in this supplement Fowden et al . 2012; (Ousey and Fowden 2012).…”
Section: Effects Of In Utero Disease On Foal Health and Future Performentioning
confidence: 99%